THE EFFICACY OF NASOGASTRIC TUBE IN A LARGE BLOOD CLOT EVACUATION DURING CYSTOSCOPY - Wallad, Caesar Khairul; Santoso, Jumadi; Adi, Kuncoro (Indonesian Journal of Urology, 2016)
Objective: In this study we introduce using nasogatric tube as an alternative to procure a safe and efficient way to remove large troublesome blood clots during cystoscopy procedure. Material & methods: We prospectively perform blood clot evacuation using nasogastric tube suction (NGT) on 21 patients in Hasan Sadikin GeneralHospital Bandung,within 6 months period. A 24 fr sheath and 16 fr NGT connected to suction unit with a 300 mmhg negative pressure was set. A repetitive back and forth technique was set in motion during the procedure. Cystoscopy time and NGT suction time was documented. Results: All patients were successfully managed with this method without complication during the procedure. The average time for clot removal was 5 minutes 8 seconds with average cystoscopy time was 20 minutes 12 seconds and average estimated blood clots volume was 483 grams. Conclusion: Evacuation using NGT suction is effective, safe and an efficient way to remove a large bothersome clots.